Evaluation of nutritional components of different foxtail millet (Setaria italica) germplasm for hay - Ren, X L; Li, S G; Cui, J H; Liu, M; Song, S J; Liu, F; Nan, C M; Wang, X G; Wang, J; Xia, X Y (The Indian Journal of Agricultural Sciences, 2020)
Foxtail millet (Setaria italica) is highly adaptable to abiotic stresses, especially drought and poor soil. At present, few studies have analysed nutritional components and evaluated the nutritional value for hay from different foxtail millet germplasm resources. The objective of this study was to improve the selection and breeding efficiency of forage foxtail millet germplasm resources, which is important for the development and growth of livestock. The contents of 11 nutritional indices in hay of 82 foxtail millet germplasms were determined during 2014-15, and correlation and clustering of nutrient quality characteristics were performed. The results indicated that there were significant difference between varieties of crude protein and crude ash (P<0.05), there were extremely significant differences between varieties of moisture, crude fibre, carbohydrate, ether extract, phosphorus, iron, calcium, zinc, selenium (P<0.01). The 82 varieties were classified into six types by hierarchical cluster analysis, including higher protein, rich in minerals, higher ether extract, and higher carbohydrate, which may be of value in the application of cultivating higher quality forage millet and functional millet grass in northern summer millet region.